Penyelesaian Sengketa Penggunaan Nama Ormas yang Sama Melalui Pendekatan Yuridis - Amirullah; Umar Aris; Papang Sapari (Syntax Literate, 2023)
Community organizations are a means to channel opinions and thoughts for community members, and have a very important role in increasing active community participation in order to realize a life of society, nation, and state that is relevant to a society that is, devout, intelligent, just and prosperous. In the form of today's community order that is no longer "strict" in the pattern of hierarchical relations, among others, by strengthening the autonomy of government management, strengthening community independence. In practice in the field, there is the same name of the CSO, namely (Forkabi) whose dispute is resolved by the Jakarta PTUN Number: 168 / G / 2021 / PTUN. JKT. The research method used is the normative juridical method, which is research that prioritizes literature data, namely research on secondary data. The secondary data can be primary, secondary or tertiary legal material. This research includes research on positive legal provisions in force in Indonesia relating to dispute resolution using the same community organization name. Based on the results of the study, the author concludes that the dispute resolution mechanism for using the same name of CSOs is through the Court, in this case the State Administrative Court which is authorized to resolve disputes over the use of the name of the legal entity of the association where there are similarities in essence between one association and another, to ascertain whether there are similarities in the name of one association with the name of another association. What is meant by "similarity in essence" is the similarity caused by the presence of dominant elements between one Brand and another Brand so as to give the impression of similarity, both regarding the form, way of placement, way of writing or combination between elements, as well as the similarity of speech sounds, contained in the Brand.